Mechanism of sodium and chloride transport in the thin ascending limb of Henle. - Imai, M (1976)
Our previous in vitro studies have disclosed that the thin ascending limb of Henle (tALH) possesses some unique membrane characteristics. In those studies we failed to demonstrated active transport of sodium chloride by the tALH, although it was shown that the isotopic permeability to sodium and chloride was unusually high. However, we did not examine the mechanisms by which the apparent high permeation of sodium chloride occurs. Thus the purpose of the present studies was to elucidate the mechanism of sodium chloride transport across the isolated tALH of the rabbit by conducting four different types of studies: (1) comparison of the observed chloride and sodium flux ratios to those predicted by Ussing's equation under imposed salt concentration gradients; (2) kinetic evaluation of chloride and sodium fluxes; (3) examination of the effect of bromide on the kinetics of chloride transport; and (4) experiments to test for the existence of exchange diffusion of chloride. In the first set of studies the predicted and the theoretical flux ratios of sodium were identical in those experiments in which sodium chloride was added either to the perfusate or to the bath. However, the observed chloride flux ratio, lumen-to-bath/bath-to-lumen, was significantly lower than that predicted from Ussing's equation when 100 mM sodium chloride was added to the bath. In the second set of experiments the apparent isotopic permeability for sodium and for chloride was measured under varying perfusate and bath NaCl concentrations. There was no statistical change in the apparent sodium permeability coefficient when the NaCl concentration was raised by varying increments from 85.5 to 309.5 mM. However, permeation of 36Cl decrease significantly with an increase in Cl from 73.6 to 598.6 mM. These events could be explained by a two component chloride transport process consisting of simple diffusion and a saturable facilitated diffusion process with a Vmax = 3.71 neq mm-1 min-1. In the third set of studies it was shown that bromide inhibits transport of chloride and that the magnitude of inhibition is dependent on chloride concentrations. The fourth set of studies ruled out the existence of exchange diffusion. In conclusion, these studies indicate that sodium transport across tALH is by simple passive diffusion, while chloride transport across tALH involves at least two mechanisms: (1) simple passive diffusion; and (2) a specific membrane interaction process (carrier-mediated) which is competitively inhibited by bromide.